Improve Creative Thinking Ability With Posing Problem Learning - Yanto, Supri; Nasution, Nasution; Wisnu, Wisnu (Universitas Negeri Surabaya, 2019)
The purpose of this study is to describe the students' creative thinking skills in social studies learning using the Problem Posing model. The subjects in this study were 28 eighth grade students of SMP Negeri 1 Tulangan academic year 2019. Researchers used primary data and data collection techniques, namely tests. Tests were carried out before and after learning. The results showed that the test results of independent sample t-test posttest creative thinking abilities of learners shows that there are differences in the ability of creative thinking between the experimental class and class control after being given treatment. Based on the analysis of the t-test, it was concluded that the problem posing learning model influenced students' creative thinking abilities. This research is useful for teachers, that is, they can develop teacher insights to be more innovative and creative in creating fun learning activities in the classroom and increasing students' knowledge competencies and creative thinking abilities. The problem posing learning model is implemented into the class because it can improve the ability of creative thinking and understanding in addressing problems and conflicts that occur in society and is expected to optimize the ability to think creatively.